منشیات کے نقصانات اور روک تھام: سیرت طیبہ کی روشنی میں: Drug Harms and Prevention: In the Light of History - Dr. Muhammad Manzar Ehsan; Dr. Sidra Ahmed; Hafiz Ahmad Mahmood (International Research Journal of Arabic and Islamic Studies, 2024)
The use of narcotics is very important social issue of current age. The of usage of narcotics are modernized in the fast-changing society. Alcohol was used by man for drinking for centuries, but in the twentieth century cannabis, opium, chars and heroin were its modern shapes. Now in the twenty first century, it is damaging the society in the fatal and ultramodern forms like glass and ice. Mostly the youngsters in the society are its target. The tragedy is that the educational institutions are not protected from the cursing of this drug. It is necessary that in order to prevent the younger generation from this social evil, the state, parents and the teachers should take measures regarding character building and prevent their future generation from this curse. The ethical spiritual religious training of the race should be done in the light of Seerat-e- Tayyba so that young generations can be the architect of the country's wealth, not to become an object of dirt and destitute for the nation and nation. It is imperative that the youth class should consider their responsibilities in positive attitude only. In the underlying article, the teachings of the Prophet (peace and blessings of Allah be upon him) have been made to offer suggestions for solving this very important social problem.